Brazilian criminal organizations as subjects of non-classical wars in the form of criminal rebellion - Strigunov, K. S. (Vestnik Moskovskogo universiteta. Seriâ 25. Meždunarodnye otnošeniâ i mirovaâ politika (Online), 2024)
Modern criminal organizations are increasingly destabilizing both individual states and the international system in general. As they reach a certain level of development, they are able to undermine the sovereignty and territorial integrity of states through the establishment of control over parts of their territories. This can lead to a situation of criminal rebellion, understood as a mechanism of confrontation with the state under which organized crime begins to pose a challenge to the very existence of the latter. In this regard, the case of Latin American and Caribbean countries and, in particular, Brazil is of special interest. The first section examines academic discussions regarding the applicability of the concepts of ‘internal armed conflict’ and ‘unconventional warfare’ to the situation of criminal rebellion in Brazil. Special attention is paid to two key criteria — the intensity of violence and the organizational level of the belligerent parties. The author concludes that with regard to both these criteria, there is a state of unconventional warfare in Brazil in the form of a criminal rebellion that has reached the level of the internal armed conflict. The second and third sections of the paper examine the factors that contributed to the transformation of specific Brazilian criminal organizations — the ‘First Capital Command’ (PCC) and the ‘militias’ — into actors of a full-fledged criminal rebellion. In the case of the PCC, these factors include the adoption of more flexible network organizational principles and the guerrilla tactics, accompanied by the growing internationalization of criminal activities, against the backdrop of further militarization of the Brazilian police. In the case of the ‘militias’, the author focuses on the concept of ‘armed politics’, which describes a situation where organized crime pervades the entire state apparatus. The author concludes that the situation in Brazil shows all the signs of a criminal insurgency, when certain criminal organizations have reached such a level of organizational complexity that they are able to undermine the sovereignty of the state by establishing control over at least part of its territory and acting as a belligerent in the internal armed conflict. The specific of the situation in Brazil is that such an insurgency is carried out by non-state violent actors who formally do not pursue any political/ideological goals. However, due to their destructive potential they should be treated as if they had political goals.